STRATEGI MANAJEMEN PERSEDIAAN HALAL DALAM MITIGASI RISIKO GHARAR : TINJAUAN KEPATUHAN RANTAI PASOK BERBASIS SYARIAH - Muhammad Alif; Sultan Muhammad Hafidz; Venotty Ananda Putri (Taksasila Edukasi Insani, 2026)
Halal inventory management within the supply chain faces critical challenges regarding Gharar (uncertainty) risks, which can undermine product integrity and the validity of muamalah contracts. This research aims to formulate a halal inventory management strategy as a mitigation mechanism for Gharar risks within the framework of Sharia Supply Chain Management (SSCM). The method employed is a Systematic Literature Review (SLR), analyzing indexed scientific literature and authoritative Sharia sources from 2020-2025. The results indicate that quality and quantity Gharar risks in warehousing can be effectively mitigated through the integration of modern operational strategies and Sharia principles. Key findings include the effectiveness of physical segregation to prevent ikhtilath, the application of Just-in-Time (JIT) philosophy to ensure Thayyib principles, and the use of traceability technology to ensure transparency (bayan) of product origin. This study concludes that Sharia-based inventory management is not merely formal regulatory compliance but a strategic model to ensure transactional fairness and blessings across the halal value chain.Keywords : Halal Inventory Management, Sharia Supply Chain (SSCM), Gharar Risk, Traceability